2022
DOI: 10.1002/jcla.24208
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the overexpression of theERG‐11,MDR‐1,CDR‐1, andCDR‐2genes in fluconazole‐resistantCandida albicansisolated from Ahvazian cancer patients with oral candidiasis

Abstract: Introduction Resistance to azole drugs has been observed in candidiasis due to their long‐term use and poor response to treatment. Resistance to azole drugs in Candida albicans isolates is controlled by several genes including ERG11, CDR1, CDR2, and MDR1. In this study, the expression of the mentioned genes was evaluated in C. albicans isolates susceptible and resistant to fluconazole. Methods After identifying the Candida isolates using morphological and molecular methods, the minimum inhibitory concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Candida albicans is the most causative agent of candidiasis, especially in critical and immunocompromised patients. One of the challenges in developing new antifungal drugs is the overexpression of the CDR1 and CDR2 efflux pumps that cause resistance against the common antifungal medications ( 17 ). Emerging ILs with unique properties of the elongated against the fungal agents, lead the researchers to apply them as new safe administrations against fungi ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Candida albicans is the most causative agent of candidiasis, especially in critical and immunocompromised patients. One of the challenges in developing new antifungal drugs is the overexpression of the CDR1 and CDR2 efflux pumps that cause resistance against the common antifungal medications ( 17 ). Emerging ILs with unique properties of the elongated against the fungal agents, lead the researchers to apply them as new safe administrations against fungi ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the challenges in developing new antifungal drugs is the overexpression of the CDR1 and CDR2 efflux pumps that cause resistance against the common antifungal medications ( 17 ). Emerging ILs with unique properties of the elongated against the fungal agents, lead the researchers to apply them as new safe administrations against fungi ( 17 ). Some of the investigators demonstrated the antimicrobial function of various ionic liquids ( 12 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, these authors also verified that AgNPs treatment reduced the membrane content of Cdr1p and Cdr2p, and thus efflux pump activity. FCZ-resistant C. albicans strains usually exhibit overexpression or increased efflux pump activity, which reduces their susceptibility to antifungal agents [ 48 , 49 ]. In this case, exposure to AgNPs restored the FCZ susceptibility phenotype of the resistant strains.…”
Section: Metal Nanoparticlesmentioning
confidence: 99%